PENGARUH TERAPI HEALING TOUCH TERHADAP PERUBAHAN TEKANAN DARAH PASIEN HIPERTENSI DI DESA TULAKAN DONOROJO JEPARA - Sukarmin, Sukarmin (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2016)
Background : Hypertension is a disease that can not be cured but can be controlled , it requires patience and the cost is quite expensive . Therefore it takes effort to make non- pharmacological treatment , one of them with a touch therapy . Objective: To determine the effect of therapeutic touch on changes in blood pressure in hypertensive patients in the Village District of Donorojo Tulakan Jepara .. Method: quantitative research , while the design in use is pretest - posttest control group design . In this design there are two groups of randomly selected , 38 samples were used as samples . Results: The results of testing the effect of healing touch therapy to changes in blood pressure in patients with hypertension showed that the statistical analysis obtained by Wilcoxon test ( p value = 0.000 ) is smaller than ( α = 0.05 ) , it can be concluded that there is the effect of touch therapy on blood pressure ( systolic and diastolic ) in hypertensive patients . Conclusion : There is significant influence between the effect of touch therapy on blood pressure ( systolic and diastolic ) in hypertensive patients Tulakan Village District of Jepara Donorojo